Implicit Contextual Learning in Prodromal and Early Stage Huntington's Disease Patients - Marieke van Asselen; Inês Almeida; Filipa Júlio; Januário, C.; Bobrowicz-Campos, E.; Simões, M.; Miguel Castelo-Branco (Journal of the International Neuropsychological Society, 2012)
Huntington’s disease (HD) is a genetic neurodegenerative disorder affecting the basal ganglia. These subcortical structures are particularly important for motor functions, response selection and implicit learning. In the current study, we have assessed prodromal and symptomatic HD participants with an implicit contextual learning task that is not based on motor learning, but on a purely visual implicit learning mechanism. We used an implicit contextual learning task in which subjects need to locate a target among several distractors. In half of the trials, the positions of the distractors and target stimuli were repeated. By memorizing this contextual information, attention can be guided faster to the target stimulus. Nine symptomatic HD participants, 16 prodromal HD participants and 22 control subjects were included. We found that the responses of the control subjects were faster for the repeated trials than for the new trials, indicating that their visual search was facilitated when repeated contextual information was present. In contrast, no difference in response times between the repeated and new trials was found for the symptomatic and prodromal HD participants. The results of the current study indicate that both prodromal and symptomatic HD participants are impaired on an implicit contextual learning task.